Socioeconomic and Health-Related Factors Associated with Chronic Energy Deficiency among Pregnant Women: A Cross-Sectional Study - Dewi, Eva Ratna; Pangaribuan, Ingka Kristina; Sinaga, Ribur; Miftasari, Kiki (Journal of Applied Nursing and Health, 2026)
Background: Pregnant women are a vulnerable group to nutritional problems, particularly Chronic Energy Deficiency (CED). Despite various efforts to improve the nutritional status of pregnant women, the prevalence of CED in the Lintang region remains high. Evidence regarding the determinants of CED in remote and resource-limited areas is limited, and few studies have specifically examined this issue in this area. This study aimed to analyze factors associated with CED among pregnant women. Methods: This study used a cross-sectional design with a quantitative approach. The sample consisted of 60 pregnant women who met the inclusion and exclusion criteria. The variables studied included Education, income, parity, and history of infectious diseases as factors influencing CED. Data were analyzed using the chi-square test, with effect sizes in the form of odds ratios (ORs) and 95% confidence intervals. Results: This study showed a significant association between Education (OR = 3.25; p = 0.008), income (OR = 3.45; p = 0.007), parity (OR = 2.95; p = 0.007), and history of infectious diseases (OR = 2.85; p = 0.016) with the incidence of CED among pregnant women. Although these results were statistically significant, conclusions should be viewed with caution, given the observational nature of the analysis. Conclusion: Socioeconomic and health factors play a significant role in the incidence of CED among pregnant women in this area. To reduce the prevalence of CED, integrated interventions, including nutrition education, economic support, and infectious disease prevention, are needed, particularly in remote areas with limited access to health services. These findings provide important insights for health policy development and further research with more comprehensive designs.